(untitled) (Physical Education, Health and Social Sciences, 2024)
This study investigates the perceptions of educated parents regarding their children’s participation in sports within District Mardan. Based on comprehensive data analysis, key findings emerged from a sample of 50 educated parents selected through simple random sampling. The results indicate that nearly all children were encouraged by their parents to engage in sports, reflecting a general belief among respondents that parents support their children’s sports participation. Although most teachers provide adequate sports facilities in schools, such resources are often lacking at home. Notably, parents demonstrated strong encouragement for female participation in sports, frequently acknowledging their achievements. However, many parents expressed dissatisfaction with the current level of their children’s involvement in sports. Additionally, the findings highlight a consensus among parents that sports activities serve as an essential avenue for skill development and enhance cognitive abilities, positively impacting academic performance. Data was collected using a structured questionnaire developed under the guidance of experts in sports sciences and physical education, providing a robust framework for understanding parental perceptions in this context. Key words: Parental Perception, Sports Participation, Educated Parents Skill Development, Gender Encouragement